How Does Concurrency Extend The Paradigm Of Computation?[a]. - Schachter, Vincent (Monist, 1999)
Discusses the role of concurrency in the extension of the notion of computation. Expressive of concurrent and sequential models; Boundaries of the Church-Turing thesis framework; Phenomena arising from the representation of concurrent systems leading to the concurrency theories; Conceptual operations captured by process algebras; Concurrency models' impact on the toolbox for modeling real-world complex systems.